Factors affecting age at presentation of Autism Spectrum Disorders; A descriptive survey from a child mental health clinic at Lady Ridge(way Hospital - Dahanayake, D.M.A.; Rohanachandra, Y.M.; Wijetunge, G.S. (Sri Lanka Journal of Psychiatry, 2015)
Attached

Background Early diagnosis o f au tism is im p o rta n t since Early In te n s iv e B e h a v io u ra l In te r v e n tio n s im p ro v e s o u tc o m e . A ge a t p re s e n ta tio n to child psychiatry services in Sri Lanka and th e factors determ inin g it have not been established. These w ould be useful in planning service provision. The objective o f this study w as to assess th e patterns and factors affecting age a t p res en tatio n o f ch ildren w ith au tism to a child m ental health clinic a t Lady Ridgeway Hospital. M e th o d All patients diagnosed as having autism registered at a child m ental health clinic a t Lady Ridgeway Hospital fro m January to D ecem b er 20 13 w e re included. Data w as collected retrospectively fro m clinic records. Results H alf o f th e participants had presented a t th e age o f 3 ye ars o r less. S peech d e la y w as th e c o m m o n e s t presenting co m p lain t (5 8.5% ). Age a t presentatio n show ed a significant association w ith th e natu re o f th e presen tin g sym p tom s, w ith ch ild ren w h o had speech delay presenting a t an e a rlie r age (p = 0.02). Th ere was no significant association b e tw ee n age at p re s e n ta tio n an d g e n d e r o f th e c h ild , p a re n ta l ed u catio n level, incom e o r w h e th e r th e child w as living w ith extended fam ily. Conclusion Speech delay is th e com m onest reason fo r children w ith autism to be brought to health services, and it m ay prom pt early presentation. Education ab ou t o th er s y m p to m s m a y fu r t h e r h e lp to e n s u re e a rly presentation.
Keywords: autism; speech delay; age at presentation